MOBILITY MOVEMENT PATTERNS TRAITS FOR ROUTING PROTOCOL (International Journal of Engineering and Computer Science, 2014)
Mobile Ad-Hoc Network is dynamic infrastructure based network of mobile nodes. Nodes are connected by wireless links to form random topology without the use of existing infrastructure. It consists of a number of mobile nodes that uses data packets through a wireless medium. In all the routing protocols, mobility of a node is one of the vital characteristics in determining the by and large performance of the ad hoc network, so it is necessary to know about various movement mobility models and their effect on the routing protocols. In this paper, we have compared different mobility models. The performance of mobile ad-hoc network protocol change significantly with the change of the mobility model.